Gliding arc discharge non-thermal plasma for retardation of mango anthracnose - Khanh Thi Kim Phan (2019)
© 2019 Elsevier Ltd The effects of non-thermal plasma (NTP) using a gliding arc (GA) discharge was studied with harvested Nam Dok Mai mangoes to determine the rate of retardation of anthracnose disease (Colletotrichum gloeosporioides). Different fluxes of argon (Ar) gas (3–5 L/min) and treatment times (5–7 min) with NTP delayed mycelium growth as well as decreasing fungal spore survival and anthracnose severity. A GA discharge at 5 L/min Ar for 7 min had a significantly higher (p ≤ 0.05) inhibition of C. gloeosporioides mold growth on potato dextrose agar and mango fruit at 30 °C together with reducing the number of fungi spores in suspension. Hydroxyl radicals (OH ● ) together with hydrogen peroxide (H 2 O 2 ) may be responsible for the suppression of the postharvest anthracnose disease with mangoes.